Wind Energy Fed UPQC System for Power Quality Improvement - Sarita Samal; Prakash Kumar Hota (Bulletin of Electrical Engineering and Informatics, 2018)
The extensive use of non-linear loads in domestic, industrialand commercial services origin harmonic complications.Harmonics make malfunctions in profound equipment, voltage drop across the network, conductor heat increases and overvoltage through resonance. All these problems can be remunerated by using Unified Power Quality Controller (UPQC) and the operation of UPQC depends upon the available voltage across capacitor present in dc link. If the capacitor voltage is maintained constant then it gives satisfactory performance. The proposed research is basically on designing of Wind energy fed to the dc link capacitor of UPQCso as to maintain propervoltageacross it and operate the UPQC for power quality analysis. The proposed technique is the grouping of shunt and series Active Power Filter (APF) to form UPQC which is fed wind energy system and connected to grid for better response in the output. In this paper, the simulation model of series APF, shunt APF, UPQC and Wind energy with UPQC are design in Matlab. The proposed Wind energy-UPQC is design in Matlab simulation for reduction of voltage sag, swell, harmonics in load current and compensation of active and reactive power.